The Reliability, Validity and Normative Scores of the Bene-Anthony Family Relations Test for Use With Arab Children - Soliman, Abdrabo; Abdel-Salam, Abdel-Salam G.; Ahmed, Mervat (Frontiers in Psychology, 2021)
Background: The Bene-Anthony Family Relations test (BAFRT) is one of the most widely used measures of family dynamics seen from a child’s perspective. However, the most common issue surrounding this test is the lack of accurate normative scores for use with non-white ethnic groups. The purpose of this study was to examine the BAFRT’s reliability and validity for use with Arab children, as well as to provide normative data for this group. Methods: The BAFRT was translated into Arabic and back-translated to ensure accuracy. The test was administered to a cohort of 394 Arab children, consisting of both cognitively normal children (n = 269) and children diagnosed with a psychological disorder (n = 125), all aged 5-8 years old. Test-retest reliability was assessed using a sub-set of children and validity was tested against clinical status as well as CBCL and SDQ measures. Normative measures were calculated after examining the impact of influencing variables such as age and gender. Results: Statistical analyses showed that in our cohort of Arab children the BAFRT has good test-retest reliability, correlates well with measures of emotional and behavioural adjustment, and discriminates accurately between clinical and non-clinical children. Age, gender and clinical status all significantly impacted upon BAFRT scores and therefore normative values are presented from our cohort when considering these variables. Conclusions: The normative scores we present will provide researchers and clinicians an appropriate reference point for the comparison of scores from Arab children and a starting point for future research into this area. Keywords: Family dynamics, Arab children, Bene-Anthony Family Relations Test, normative scores, reliability, validity. Abbreviations: The Bene-Anthony Family Relations test (BAFRT); Child Behaviour Checklist (CBCL); Prosocial Behaviour Strengths and Difficulties Questionnaire (SDQ)